The Implementation of Augmented Reality Technology in Teaching Natural Sciences to Improve Elementary Students' Learning Achievement - Ali Fakhrudin (State Institute of Islamic Studies Imam Bonjol Padang, 2018)
In this research, the researcher developed new innovation in natural sciences learning of elementary school by implementing augmented reality technology. The method that used in this research was research and development method based on Borg and Gall theory which consists often stages: 1) research and information collecting, 2) planning, 3) develop preliminary for more product, 4) preliminary field testing, 5) main product revision, 6) main field testing, 7) operational product revision, 8) operational field testing, 9) final product revision, 10) dissemination and implementation. The result of this research is learning media of natural sciences learning in elementary school by utilizing augmented reality technology. Based on the implementation of experiment, it is obtained the data that learning process using augmented reality which is developed can improve the students' learning achievement.